Intracellular localization of 125I-labeled insulin in hepatocytes from intact rat liver. - Carpentier, J L (1979)
We have shown that 125I-labeled insulin initially localizes to the plasma membrane of isolated rat hepatocytes. The ligand is subsequently internalized and preferentially localizes to lysosomal structures. Further, we have observed that labeled insulin localizes to regions of the cell rich in lysosomal and Golgi elements. In the present study in intact rat liver we found that, approximately 10 min after a pulse injection of 125I-labeled insulin, 56% of the label was internalized by the cell. When all grains are considered there is a preferential localization of grains to the biliary pole of the cell and these grains are almost all internalized and preferentially associated with lysosomes. These data, therefore, demonstrate that the lysosome-Golgi-rich area of the isolated hepatocyte corresponds to the biliary pole of the cell and there is a movement of the labeled hormone from its initial binding site on the plasma face of the cell membrane toward the biliary pole of the cell.